Beads-Based Electrochemical Assay for the Detection of Influenza Hemagglutinin Labeled with CdTe Quantum Dots - Krejčová, Ludmila; Nejdl, Lukáš; Hynek, David; Křížková, Soňa; Kopel, Pavel; Adam, Vojtěch; Kizek, René (MDPI, 2013)
In this study we describe a beads-based assay for rapid, sensitive and specific isolation and detection of influenza vaccine hemagglutinin (HA). Amplification of the hemagglutinin signal resulted from binding of an electrochemical label as quantum dots (QDs). For detection of the metal and protein part of the resulting HA-CdTe complex, two differential pulse voltammetric methods were used. The procedure includes automated robotic isolation and electrochemical analysis of the isolated product. The isolation procedure was based on the binding of paramagnetic particles (MPs) with glycan (Gly), where glycan was used as the specific receptor for linkage of the QD-labeled hemagglutinin.

In this study we describe a beads-based assay for rapid, sensitive and specific isolation and detection of influenza vaccine hemagglutinin (HA). Amplification of the hemagglutinin signal resulted from binding of an electrochemical label as quantum dots (QDs). For detection of the metal and protein part of the resulting HA-CdTe complex, two differential pulse voltammetric methods were used. The procedure includes automated robotic isolation and electrochemical analysis of the isolated product. The isolation procedure was based on the binding of paramagnetic particles (MPs) with glycan (Gly), where glycan was used as the specific receptor for linkage of the QD-labeled hemagglutinin.
Beads-Based Electrochemical Assay for the Detection of Influenza Hemagglutinin Labeled with CdTe Quantum Dots
Keywords: influenza hemagglutinin; electrochemical detection; paramagnetic particles; glycan; quantum dot labeling; influenza hemagglutinin; electrochemical detection; paramagnetic particles; glycan; quantum dot labeling